Le rôle du testing cognitif en orientation auprès des élèves de la formation professionelle - Noelting, Gérald; Chabot, Nathalie (Canadian Journal of Counselling and Psychotherapy, 2011)
Concepts and methods resulting from research in cognitive psychology on cognitive styles and conceptual levels should be used more frequently in counselling in order to identify the potential of students enroled in professional training programs. In fact, within the system of professional training, it is often useful to identify not only specific attitudes but the place and role played by dimensions such as dependence-independence toward the field (cognitive style), strategies for resolving problems based on Piaget-type tests, and the concept of self in school. When we talk about the future of psychological tests in professional training, we must not under-estimate the importance of more cognitive tests as, in the last analysis, the way in which an individual processes information, his/her cognitive style and his/her self-concept as learner are all factors as much liable to lead to success in a trade as in a so-called "more academic" profession.